Response Planning for Wildlife Rehabilitation Centers: An Infectious Disease Management Policy— Highly Pathogenic Avian Influenza - Willette, Michelle; Schott, Renée (Wildlife Rehabilitation Bulletin, 2017)
Free–ranging and captive wildlife can serve as reservoirs for pathogenic diseases in humans, livestock, or poultry. In contrast to zoological institutions, there has been little to no infectious disease response planning by managed captive avian wildlife facilities such as wildlife or raptor rehabilitation centers. It is incumbent upon each managed captive wildlife facility to assure regulators that the facility and its operations do not pose a threat to public health or animal agriculture. This is accomplished by working with local regulators and stakeholders to develop infectious disease policies and management plans appropriate to each facility in order to protect staff, volunteers and the general public, animal agriculture, wild animals, and the environment. In 2014, highly pathogenic avian influenza virus (HPAIV) originating from Eurasia spread along wild bird migratory pathways into North America. This paper uses HPAIV as an example to assist facilities in developing an effective infectious disease management policy.